Wordwall Application as a Media to Improve Arabic Vocabulary Mastery of Junior High School Students - Fakhruddin, Abdul Aziz; Firdaus, Mochammad; Mauludiyah, Lailatul (Arabiyatuna: Jurnal Bahasa Arab, 2021)
This study used wordwall application as a learning medium based on educational games. This study aims to determine the effectiveness of the wordwall application in increasing the mastery of Arabic vocabulary. This research used a quantitative approach with the research subjects of class VIII. The type of research is quantitative associative which aims to determine the effect or relationship between two or more variables. The data collection methods were interviews, questionnaires, tests, and documentation. The data analysis used a comparative analysis by comparing the pretest and posttest values (related sample t-test). This study revealed the following: (1) Media creation was done by logging into wordwall.net in order to be able to choose the desired shape according to certain needs. (2) There was a significant difference in terms of the pretest score which is smaller than the posttest score (45.63 < 77.50), (3) there was a difference in the average pretest and posttest outcomes with sig value of 0.000 (<0.05). (4) The percentage of N-Gain was 56.6%, which was categorized as quite effective. Based on the data analysis, it was concluded that the wordwall application was quite effective in increasing the mastery of Arabic vocabulary (Students mastered 25 vocabularies for each theme and according to government standards). Furthermore, the wordwall application could increase the fun, interest, enthusiasm and motivation of students in learning Arabic vocabulary.